![image](https://tex.z-dn.net/?f=%282x%2B1%29%282x-1%29%3E2%2A%28x%2B0.5%29%5E%7B2%7D+%5C%5C4+x%5E%7B2%7D+-1%3E2%28+x%5E%7B2%7D+%2B0.25%2Bx%29%5C%5C4+x%5E%7B2%7D+-1%3E2+x%5E%7B2%7D+%2B0.5%2B2x%5C%5C4+x%5E%7B2%7D+-1-2+x%5E%7B2%7D+-0.5-2x%3E0%5C%5C2+x%5E%7B2%7D+-2x-1.5%3E0%5C%5C2+x%5E%7B2%7D+-2x-1.5%3D0+%5C%5C+D%3D4%2B12%3D16%5C%5C+%5Csqrt%7BD%7D+%3D4%5C%5C++x_%7B1%7D+%3D+%5Cfrac%7B2%2B4%7D%7B4%7D+%3D+%5Cfrac%7B6%7D%7B4%7D+%3D1.5%5C%5C+x_%7B2%7D+%3D+%5Cfrac%7B2-4%7D%7B4%7D+%3D+%5Cfrac%7B-2%7D%7B4%7D+%3D-0.5%5C%5C2+x%5E%7B2%7D+-2x-1.5%3D2%28x%2B0.5%29%28x-1.5%29+)
2*(x+0.5)^{2} \\4 x^{2} -1>2( x^{2} +0.25+x)\\4 x^{2} -1>2 x^{2} +0.5+2x\\4 x^{2} -1-2 x^{2} -0.5-2x>0\\2 x^{2} -2x-1.5>0\\2 x^{2} -2x-1.5=0 \\ D=4+12=16\\ \sqrt{D} =4\\ x_{1} = \frac{2+4}{4} = \frac{6}{4} =1.5\\ x_{2} = \frac{2-4}{4} = \frac{-2}{4} =-0.5\\2 x^{2} -2x-1.5=2(x+0.5)(x-1.5) " alt="(2x+1)(2x-1)>2*(x+0.5)^{2} \\4 x^{2} -1>2( x^{2} +0.25+x)\\4 x^{2} -1>2 x^{2} +0.5+2x\\4 x^{2} -1-2 x^{2} -0.5-2x>0\\2 x^{2} -2x-1.5>0\\2 x^{2} -2x-1.5=0 \\ D=4+12=16\\ \sqrt{D} =4\\ x_{1} = \frac{2+4}{4} = \frac{6}{4} =1.5\\ x_{2} = \frac{2-4}{4} = \frac{-2}{4} =-0.5\\2 x^{2} -2x-1.5=2(x+0.5)(x-1.5) " align="absmiddle" class="latex-formula">
+ - +
-------------|---------------------------|------------------------->
-0.5 1.5 x
x∈
Ответ: x∈